Hospital lung surgery volume and patient outcomes. (March 2019) - Thai, A.A.; Stuart, E.; te Marvelde, L.; Milne, R.L.; Knight, S.; Whitfield, K.; Mitchell, P.
Highlights: Historical data suggests an association between survival and the number of surgeries done at a hospital. In our Australian study, we found no evidence of survival differences in patients between low- and high-volume hospitals for lung cancer surgery. A higher proportion of patients had an ICU admission ≥24 h in lower volume centres. Abstract: Objectives: There has been evidence of an association between patient outcomes and the number of surgeries performed at a hospital. To our knowledge, there are no Australian data on hospital cancer surgery volumes and patient outcomes. We evaluated the relationship between hospital non-small cell lung cancer (NSCLC) surgery volume and patient outcomes in Victoria. Materials and methods: Patients with a primary diagnosis of NSCLC between 2008 and 2014 were identified in the Victorian Cancer Registry (n = 15, 369), 3, 420 (22%) of whom had lung cancer surgery. Primary outcome was death within 90 days of surgery and secondary outcomes included overall survival, use of postoperative ventilation and ≥24hours spent in ICU. Hospital volume was measured as the average number of lung surgeries performed per year, with quartiles Q1: 1–17, Q2: 18–34, Q3: 35–58 and Q4: 59 + . Results: 57% (1, 941/3, 420) lung cancer patients underwent lobectomy, 38% (1, 299/3, 420) sub-lobar resection and 5% (180/3, 420) pneumonectomy. The overall 90-day mortality after lung surgery was 3.5%, and was 2.6% and 4.5% for patients undergoing lobectomy and sub-lobar resection respectively. There was no difference in 90-day mortality and overall survival between low- and high-volume centres regardless of procedure. Patients operated on in lower volume centres had more admissions to ICU ≥24hours (Q1. 55% vs. Q4. 11%, p-trend <0.001). A higher proportion of patients attending private hospitals (19%) had an ASA score of 4 compared with patients attending a public hospital (9%). Conclusion: We observed no evidence of survival differences between lung cancer patients attending low- and high-volume hospitals for cancer surgery. A higher proportion of patients had an ICU admission ≥24hours in lower volume centres and there are a higher proportion of patients with an ASA score of 4 in private hospitals compared to public hospitals.